Ground Water Depth Prediction Mathematical Model Based On Geopathic Stress, Body Voltage And Skin Resistance. - et. al., Aishwarya Gawand, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper attempts to contribute to the research by 2 Mathematical models – First model relating the body voltage of a person measured on the geopathic stress zone locations with the groundwater depth, second the Skin resistance of a person measured on the geopathic stress zone locations with the ground water depth. In this paper, geopathic stress is one of the causes which affects skin resistanceand body voltage of any human being.